Knowledge and practices of infection control among healthcare workers in a tertiary care hospital - Riasat, Rabia; Malik, Minaal Ahmed; Yousaf, Iftekhar; Imam, Kamil Asghar (Pakistan Journal of Physiology, 2019)
Background: Healthcare associated infections (HCAIs) pose increasing danger to healthcare service providers and patients. This study was planned to evaluate and compare knowledge and practices of two groups of healthcare workers (doctors and nurses) in a tertiary care hospital and to highlight their role in dissemination of healthcare associated infections. Methodology: This cross-sectional analytical study was conducted at Pak-Emirates Military Hospital, Rawalpindi, Pakistan over course of 6 months. A sample of 250 was taken using convenience sampling. Study groups comprised of qualified practicing doctors and nurses. A questionnaire was self-administered amongst the study groups and was filled under supervision after voluntary consent. Data collected were analysed using SPSS-22. Results: A total of 198 responses were analysed, 83 being nurses and 115 doctors. Most respondents (83.8%) correctly identified hand washing as the most effective method to prevent HCAIs with doctors having better knowledge than nurses (63.1%). Majority (97.5%) agreed that avoiding injury with sharps, use of barrier precaution (97.5%) and hand hygiene (98.0%) effectively prevent HCAIs. There were no differences in the infection control practices of doctors and nurses (p=0.456). Females had better knowledge (54.1%±2.50) than their male counterparts (p=0.001) regarding HCAIs. Conclusion: Gaps have been identified in knowledge and practices of both groups of healthcare workers highlighting the need for periodic refresher trainings and development of a system for monitoring safe practices. Nurses exhibited greater deficit in knowledge variable than doctors suggesting the need for increased education of nurses through workshops, seminars and/or extensive curricular programmes. Pak J Physiol 2019;15(4):46?8